2022
DOI: 10.34208/jba.v24i2.1133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corporate Governance Mechanism and Operating Cash Flow on Financial Distress

Abstract: This study aims to examine the effect of corporate governance mechanisms and operating cash flows on financial distress. The variable of corporate governance mechanism is measured through managerial ownership, institutional ownership, and audit committee. Managerial ownership can reduce conflicts of interest between principals and agents, while institutional ownership and audit committees are related to increasing supervision over company management. So, a good corporate governance mechanism can avoid financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…The reason why this research uses the type of manufacturing companies is because manufacturing companies are the largest companies listed on the Indonesia Stock Exchange, besides manufacturing companies are one of the types of companies that contribute the most carbon emissions in Indonesia. In this study, financial distress is measured using operating cash flow adequacy [5] and Altman Z-score value [6]. This study uses the Common Effect Model (CEM) and Random Effect Model (REM).…”
Section: Methodsmentioning
confidence: 99%
“…The reason why this research uses the type of manufacturing companies is because manufacturing companies are the largest companies listed on the Indonesia Stock Exchange, besides manufacturing companies are one of the types of companies that contribute the most carbon emissions in Indonesia. In this study, financial distress is measured using operating cash flow adequacy [5] and Altman Z-score value [6]. This study uses the Common Effect Model (CEM) and Random Effect Model (REM).…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that cash flow ratio had a negative effect, and firm size had no effect on financial distress. Sembiring (2022) examined the effect of corporate governance mechanisms and operating cash flows on financial distress. The study used data from manufacturing companies with negative EBIT values for two years from 2017-2019.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Researchers use operational cash flow because the adequacy of operational cash flow is able to show the company"s ability to finance the company's operations and pay debts due. Sembiring (2022) [18] states that companies that do not have sufficient operating cash have a greater probability of experiencing financial distress than companies that have sufficient operating cash.…”
Section: Variable Operational Definitionmentioning
confidence: 99%